The history of formation of legal english language: the current problems of globalization of legal language (Eurasian Journal of Philology Science and Education, 2022)
The article discusses the history of emergence and development of legal language in England, as well as the role of Latin and French in its formation. Latin is still an integral part of legal language since Latin dominated in almost all of medieval Europe, and legal documents were written in Latin for many centuries. The legal language has a complex terminology, and it is often used not only by people of the legal profession, but also by ordinary, unprepared people when entering into civil law relationships in the form of contracts of sale, lease, and loan. However, they do not always understand the legal terms. In order to understand the legal language, it is necessary to turn to the history and analyze whether it is possible to create a universal legal language in the realities of the modern world. Since the beginning of the 20th century, the term legalese has appeared in legal linguistics, which means the legal language used by lawyers, especially when drafting legal documents. Legal language is filled not only with legal jargons, but also with archaism, technical terms and even expressions used in ordinary language, which has a different meaning for a lawyer. The purpose of this study is to examine the history of the emergence of legal language in England, the terminology of law, as well as to discuss problems associated with legal terminology in the era of globalization. The analysis shows that legal dictionaries in the English language continue to be replenished with neologisms, but the international society is not ready to create a single universal language of legal terms. Key words: legal language, legal language in English, neologism, globalization.